The 1904 version of Leos Jancek's Jenufa: sources, reconstruction, commentary - Audus, Mark (2008)
The main part of the thesis comprises a two-volume reconstruction of the full score of the 1904 premiere version of Janacek's opera Jenufa (volumes II/1, II/2 and II/3). Jenufa was the work that belatedly brought Janacek first to national and then to international attention as an opera composer of the first rank, yet the version heard at the Brno premiere in 1904 had until recently been unheard since 1906. This is also the first completely newly-set edition of the full score in any version for nearly four decades.